COMPARATIVE ANALYSIS OF UZBEK AND ENGLISH SENTENCE STRUCTURES IN ACADEMIC WRITING (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article deals with Uzbek and English sentence structure differences in academic writing. The paper compares syntactic features of the two languages and explains how these differences are manifested in Uzbek students' English essays. Drawing on a qualitative analysis of 30 academic essays and 5 authentic Uzbek texts, the paper reveals main problems such as word order interference, lack of articles, and misuse of passive voice. The findings show that explicit contrastive grammar instruction can improve students' writing.